Оптимизация структуры многоячейкового транзисторного преобразователя - Bondarenko, Yu. V.; Bondarenko, A. F.; Safronov, P. S.; Sydorets, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
To optimize the structure of multicell-type transistor converter with combined control it is proposed to use an additive criterion, wich would take into account such particular criteria as efficiency, cost and construction volume of the converter.